Uncertainty, social norms and consumption theory: Post and New Keynesian approaches - Jan-Oliver Menz (Intervention. European Journal of Economics and Economic Policies, 2010)
Consumption theory has always been a neglected field in post-Keynesian economics, whereas it is at the center of New Keynesian economics. This paper investigates similarities and differences between the two approaches. I will show that the newer mainstream models indeed give results that are fairly similar to traditional Keynesian ideas, even if differences – especially concerning methodological questions – still remain. Building on insights from Economic Sociology and Behavioral Economics, the importance for consumption theory of an adequate treatment of risk and uncertainty on the one hand, and the role of social norms on the other hand are emphasized.
Keywords: E21; E12; D11; 330; uncertainty; social norms; consumption theory; post-Keynesianism; New Keynesianism